2008
DOI: 10.3390/ijms9040638
|View full text |Cite
|
Sign up to set email alerts
|

Specific siRNA Targeting the Receptor for Advanced Glycation End Products Inhibits Experimental Hepatic Fibrosis in Rats

Abstract: Receptor for advanced glycation end products (RAGE) was studied in different stages of carbon tetrachloride induced hepatic fibrosis (HF), and effect of its gene silencing in the HF development was evaluated in rats. Silencing RAGE expression by specific siRNA effectively suppressed NF-κB activity, hepatic stellate cell activation, and accumulation of extracellular matrix proteins in the fibrotic liver, and also greatly improved the histopathology and the ultrastructure of liver cells. These effects may be par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 49 publications
5
37
0
Order By: Relevance
“…TGFβ1, the most prominent profibrogenic cytokine; procollagen α1(Ⅰ), a precursor of the major fibrillar collagen; TIMP1, the central inhibitor of matrix metalloproteinases (MMP); and α-SMA, a marker for HSC activation [16,17] . Enhanced RAGE expression in hepatic fibrogenesis was further shown in rats with cirrhosis induced by BDL and TAA treatment, which was in line with prior findings in CCl4induced hepatic fibrosis where RAGE transcript and protein levels were upregulated until 6 wk after the completion of CCl4 treatment [35] . Differences in RAGE expression may be due to the lack of inflammation in TAA-treated animals, since TAA treatment was stopped one week prior to tissue removal.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…TGFβ1, the most prominent profibrogenic cytokine; procollagen α1(Ⅰ), a precursor of the major fibrillar collagen; TIMP1, the central inhibitor of matrix metalloproteinases (MMP); and α-SMA, a marker for HSC activation [16,17] . Enhanced RAGE expression in hepatic fibrogenesis was further shown in rats with cirrhosis induced by BDL and TAA treatment, which was in line with prior findings in CCl4induced hepatic fibrosis where RAGE transcript and protein levels were upregulated until 6 wk after the completion of CCl4 treatment [35] . Differences in RAGE expression may be due to the lack of inflammation in TAA-treated animals, since TAA treatment was stopped one week prior to tissue removal.…”
Section: Discussionsupporting
confidence: 89%
“…Hepatic RAGE expression fibrolysis-related genes in CFSC-2G or HSC-T6 HSC. Using another experimental approach Xia et al [35] showed that targeting of RAGE by specific siRNA downregulated fibrogenesis-related transcripts in vitro and in vivo. Of note, we took great care to synthesize AGE-BSA and CML-BSA in a sterile environment and to remove any remaining endotoxin contamination in the products.…”
Section: Discussionmentioning
confidence: 99%
“…This prompted the hypothesis that galectin-3 plays a supportive role in the pathogenesis of complications of metabolic disorders, i.e., a role which is exerted through a dual, tissue-specific modulation of RAGE expression, depending on the anabolic or catabolic role of the tissue in the metabolism of AGEs/ALEs. This view is supported by the observations that diabetic glomerulopathy was accelerated in transgenic mice over-expressing RAGE [89]; diabetes-induced atherogenesis was attenuated in ApoE null mice by RAGE blockade with soluble RAGE [90]; and liver fibrosis induced by administration of carbon tetrachloride to normal rats was ameliorated by RAGE silencing [91]. However, some AGE/ALE-and RAGE-independent effects of galectin-3 might also be claimed to explain these findings, especially the direct anti-inflammatory effect of this lectin at the aortic level, and the pro-fibrotic action at the hepatic level (Figure 2).…”
Section: Galectin-3 As a Disease Mediator: Animal Studiesmentioning
confidence: 88%
“…AGEs have been reported to induce HSC proliferation by inducing cell proliferation and expression of genes relevant to HSC activation [33].…”
Section: Discussionmentioning
confidence: 99%